Population perception of the role of the Pharmacist in the context of the new coronavirus pandemic (Research, Society and Development, 2021)
The aim of this article is to assess the population's perception of the role of the pharmacist in the context of the new coronavirus pandemic. This is a descriptive exploratory study with a quantitative approach carried out, via the Google Forms platform. People of both sexes, over 18 years of age, residing in Brazil were included. The questionnaire link was sent by Whatsapp, Instagram, Facebook and email. Of the 1,748 questionnaires answered were from women (64.5%), the average age of the participants was 25.3 ± 7.9 years and the majority was brown (56.8%). Almost all 96.5% considered the pharmacist to be a health professional, however 53.4% were not attended by him during the pandemic and 68.6% did not seek guidance from him. It was found that the population of this study recognized the pharmacist as a health professional on the front line against the coronavirus, but did not know how to identify his role in the face of the pandemic.